Treatment of severe personality disorders : resolution of aggression and recovery of eroticism - Kernberg, Otto F., 1928- (American Psychiatric Association Publishing, 2018)
In Treatment of Severe Personality Disorders: Resolution of Aggression and Recovery of Eroticism, the influential psychoanalyst and psychiatrist Otto Kernberg presents an integrated update of the current knowledge of personality disorders, their neurobiological and psychodynamic determinants, and a specific psychodynamic psychotherapy geared to resolve the psychopathology of these conditions -- namely, the syndrome of identity diffusion and its influence on the capacity for emotional wellbeing and gratifying relationships with significant others. The author updates the findings of the Personality Disorders Institute of the Weill Cornell Medical College Department of Psychiatry, which are derived from the empirical research and clinical investigation of severe personality disorders, and addresses the effectiveness of transference-focused psychotherapy, a specific psychodynamic treatment for these disorders developed at the Institute. The volume focuses particularly on an essential group of techniques common to all psychoanalytically derived treatments and clarifies the corresponding differential features of various psychodynamic treatment approaches. The book examines the classification of personality disorders, the way competing viewpoints have influenced the evolution of DSM-III and DSM-IV, and the impact of new knowledge on the classification of DSM-5, with emphasis on how conflicts between scientific and political considerations have hindered the classification of personality disorders in the past. It illustrates in detail how present knowledge of neurobiological structures and neurotransmitters intertwines with the psychodynamic determinants of how psychic experience is organized. It explores psychodynamic psychotherapies and contemporary developments and controversies in the field, for example, the role of interpretation in borderline pathology is examined using a clinical case, and a new formulation of supportive psychodynamic psychotherapy is described. It addresses severe narcissistic pathology -- its diagnosis, prognosis, and treatment. Specifically, the book presents an overview of treatment options for severe narcissistic personality disorder, explores the distortions in verbal communication that may arise during psychotherapy with these patients, and focuses on the differential diagnosis of antisocial behavior. It examines the diagnosis and treatment of sexual pathology, and explores the vicissitudes of the love lives of patients with severe personality disorders. It concludes with a chapter on the essential preconditions in the education of psychodynamic psychotherapists to carry out work in this field.